2021
DOI: 10.1108/ijpsm-02-2020-0049
|View full text |Cite
|
Sign up to set email alerts
|

Risk management in the public sector: a structured literature review

Abstract: PurposeRisk management (RM) is receiving increasing academic and practitioner attention in the public sector. Despite this, there is a lack of systematization of this body of knowledge. The purpose of this paper is to analyze the state of art by examining the knowledge gaps and defining the emerging themes of RM in the public sector to guide future research agendas.Design/methodology/approachThe authors conducted a structured literature review (SLR). They analyzed 63 papers, by using Scopus database, published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 60 publications
1
29
0
15
Order By: Relevance
“…In line with this notion, Murr and Carrera (2022) present a case study of how institutional logics affected the adoption and implementation of risk management practices in a governmental entity in a developing country. Murr and Carrera (2022) thus enrich the growing literature on risk management in public sector organizations (Bracci et al, 2021) by confirming the usefulness of the institutional logics perspective for analyzing accounting and control change (Damayanthi and Gooneratne, 2017;Nguyen and Hiebl, 2021). In particular, Murr and Carrera (2021) illustrate how two competing institutional logicsin this case, a traditional logic and a modernization logicconfronted the involved actors with several tensions, which could only be lifted when a Royal Order was issued that mandated that all Saudi Arabian government entities adopt and implement adequate risk management practices.…”
Section: Papers Included In This Special Issuementioning
confidence: 85%
See 1 more Smart Citation
“…In line with this notion, Murr and Carrera (2022) present a case study of how institutional logics affected the adoption and implementation of risk management practices in a governmental entity in a developing country. Murr and Carrera (2022) thus enrich the growing literature on risk management in public sector organizations (Bracci et al, 2021) by confirming the usefulness of the institutional logics perspective for analyzing accounting and control change (Damayanthi and Gooneratne, 2017;Nguyen and Hiebl, 2021). In particular, Murr and Carrera (2021) illustrate how two competing institutional logicsin this case, a traditional logic and a modernization logicconfronted the involved actors with several tensions, which could only be lifted when a Royal Order was issued that mandated that all Saudi Arabian government entities adopt and implement adequate risk management practices.…”
Section: Papers Included In This Special Issuementioning
confidence: 85%
“…These results indicate that to professionalize risk management in the public sector, translating stakeholder pressure into top management support for risk management is crucial. Similar to Murr and Carrera (2022), the study by Schäfer et al (2022) thus adds to the literature on risk management in public sector organizations (Bracci et al, 2021) by highlighting the decisive role of top managers in these companies, such as mayors and agency heads.…”
Section: Papers Included In This Special Issuementioning
confidence: 91%
“…Although several scholars have addressed economic topics in the context of the pandemic, specific research about taxation, public finances, fiscal-or tax-related issues is not reported in the academic literature. Indeed, Yang et al (2021b) note that empirical investigations of the impacts on the governmental sector are needed in relation to policy implications to better manage future disasters and crises, given the increasing importance for risk management in the public sector (Bracci et al 2021).…”
Section: Tourism Research On Covid-19 and Tax-related Issuesmentioning
confidence: 99%
“…Research exploring the adoption and implementation of RM practices in the public sector is limited (Bracci et al, 2021). Furthermore, little is known about RM practices in institutional settings where traditional norms, values and belief systems diverge from developed, western economies.…”
Section: Introductionmentioning
confidence: 99%
“…Second, as far as we know, we are among the first researchers to use the ILP in the context of RM in governmental entities. Bracci et al (2021) argued the necessity for more theorization to advance our understanding of RM in the public sector. In line with Rana et al (2019b, p. 44), we contend that an ILP can be a fruitful framework to explore the interaction of societal logics (macro-level of analysis), organizational actions (meso-level of analysis) and individual behaviors (micro-level of analysis) in understanding the dynamics of adoption and implementation of RM, clarifying how individuals handle competing institutional logics.…”
Section: Introductionmentioning
confidence: 99%